A novel P&OT-Neville’s interpolation MPPT scheme for maximum PV system energy extraction - Bhukya, Muralidhar Nayak; Kota, Venkata Reddy (International Journal of Renewable Energy Development, 2018)
Photovoltaic (PV) system posses an optimal operating pointing, termed as Maximum Power Point (MPP). Using Maximum Power Point Tracking (MPPT) algorithm, MPP of PV system has to be tracked continuously in any climatic conditions. In general, traditional Perturb and Observe (P&OT) MPP tracker is widely used among existing controllers. But, P&OT fails to harvest maximum power from solar panel, in addition oscillations around MPP results in low efficiency of the PV system. The contradiction involved in the traditional controller can be addressed as P&OT operates with a fixed step size. Hence, with large step size MPP can be reached quickly but the magnitude of oscillations around MPP are high. Similarly, when P&OT operated with tiny step size magnitude of oscillations can be reduced at the same time PV system consumes much time to reach MPP. In order to eliminate the contradiction involved with traditional MPPT scheme and effectively optimize PV system energy, this paper put forwards a hybrid MPPT scheme based on P&OT and Neville interpolation. The proposed scheme is executed in two stages. In the first stage, P&OT is operated with a large step size till the voltage reaches near to maximum point. In the second stage, Neville interpolation is used to find the maximum power point. The performance of the proposed scheme is compared with Golden Section Search (GSS) and P&OT MPPT controllers. With the proposed scheme the convergence time required to reach MPP is improved greatly. Experimental prototype is designed and developed to verify the performance of the proposed scheme. Experimental and simulation results provide enough evidence to show superiority of the proposed scheme.Article History: Received December 15th 2017; Received in revised form July 16th 2018; Accepted September 12th 2018; Available onlineHow to Cite This Article: Bhukya, M. N. and Kota, V. R. (2018) A Novel PandOT-Neville’s Interpolation MPPT Scheme for Maximum PV system energy extraction. International Journal of Renewable Energy Development, 7(3), 251-260https://dx.doi.org/10.14710/ijred.7.3.251-260